The Impact of Glass Ceilings on Women's Digital Capability Micro-Enterprise Owners with Adaptability as a Moderation - Selvy Noviniya; Anna Suzana (Majapahit Journal of Islamic Finance and Management, 2026)
This study explores the phenomenon of invisible barriers or glass ceilings and their influence on strengthening digital capabilities among women running micro-enterprises in Cirebon Regency. Furthermore, this study also examines the position of adaptability as a moderating factor that strengthens this relationship. Through the lens of Dynamic Capabilities Theory, this research starts from the hypothesis that gender-based structural pressures can actually spur women entrepreneurs to be more agile in adopting digital technology for business sustainability. The research approach applied was quantitative, involving 168 female micro-enterprise owners in Cirebon Regency as a sample. All primary data collected through questionnaires were processed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis techniques with the help of SmartPLS software. The analysis results found that the glass ceiling has a positive and significant contribution to increasing digital capability. This indicates that gender challenges often act as a catalyst for women entrepreneurs to deepen their mastery of technology. Furthermore, it was found that adaptability plays a crucial role in moderating and strengthening the correlation between the glass ceiling and digital capabilities. These findings recommend the need for strategic policies from local governments to provide digital assistance that focuses more on the resilience and adaptability aspects of women entrepreneurs.